Errors in Writing Nouns (Isim) in Imla' Learning - Sitti Fatima; Mantasiah R; Fauziah Bachtiar (Phonologie : Journal of Language and Literature, 2025)
Abstract. This study aims to obtain data about the types of errors of students in class VIII of Wahdah Islamiyah Integrated Islamic Junior High School Makassar in writing nouns (isim) in Imla' learning. This research is a qualitative descriptive research. The data in this research is the writing of nouns (isim) in imla' learning and the source of data in this research is obtained from the results of student worksheets from tests that describe the errors contained in the writing of nouns (isim) in imla' learning of class VIII students of Wahdah Islamiyah Integrated Islamic Junior High School Makassar. The instrument of this research is imla' test on nouns (isim). Data collected through imla' test on nouns (isim). The data obtained were classified into errors. From the results of data analysis, it is known that students' errors in writing nouns (isim) in imla' learning are 941 errors consisting of errors in writing hijaiyah letters as many as 404 (42.93%) errors, errors in writing letters that can and cannot be connected as many as 85 (9,03%) errors, errors in the placement of harakat as many as 293 (31.13%) errors, errors in writing alif lam shamsiyah and alif lam qamariyah as many as 23 (2.44%) errors, errors in the placement of hamzah letters as many as 92 (9.77%) errors and errors in writing Ta' letters as many as 44 (4.68%) errorsKeyword: errors, writing, nouns (isim), imla' learning